EFEKTIVITAS PASTA GIGI BAKING SODA DAN NON BAKING SODA TERHADAP PENURUNAN STAIN PADA PEROKOK - Cut Aja Nuraskin; Reca Reca (Program Studi Kesehatan Masyarakat Universitas Sari Mutiara Indonesia, 2022)
Many people do not realize that smoking habits can affect the level of dental and oral hygiene, smoking causes abnormalities of the tongue, gums, oral mucosa, palate in the form of nicotinic stomatitis, fungal infections, and causes discoloration of the te eth. Sodium bicarbonate is a chemical compound with the formula NaHCO3 belonging to the salt group and is often found in the form of white powder crystals. Where the content of sodium bicarbonate can remove stains on smokers. The purpose of this study was to determine the effectiveness of the use of toothpaste containing baking soda and non-baking soda to reduce stains in smokers.This type of research is analytic with a quasi-experimental method. The sample was used as many as 62 people then divided into 2 groups which were then checked for staining conditions before and after the use of toothpaste containing baking soda and non -baking soda.The results showed that the average tooth staining before and after brushing using toothpaste containing baking soda showed a decrease in staining on the Lobene intensity measurement as much as 0.324, lobene area as much as 0.217, combined as much as 0.541, with p = 0.000 < = 0, 1. While the average tooth staining before and after using non -baking soda toothpaste there was a decrease in stain on Lobene intensity measurements as much as 0.043, Lobene area as much as 0.016, combined as much as 0.059 , with p value = 0.116 > = 0.1.This study concluded that the use of toothpaste containing baking soda was more effective than non-baking soda toothpaste to reduce the stain index in smokers. It is suggested that the public can use toothpaste containing baking soda as an alternative to remove stains on the teeth, and pay more attention to the status of oral hygiene.